Extravagance and three other plays - Maraini, Dacia (John Cabot University Press ; Rowman and Littlefield Publishing Group, Inc : Distributed by University of Delaware Press, 2015)
This book is a collection of four theatrical works around such themes as distress, exclusion, tragedy, and society's expectations of women. It is particularly suitable for students of Italian language, gender studies, and modern Italian literature and theater.